PENINGKATAN KEMAMPUAN MAHASISWA DALAM MEMBUAT KARYA TULIS ILMIAH MELALUI PELATIHAN PUBLISH OR PERISH - Umi Baroroh; Sabarudin Sabarudin; Mahariah Mahariah; Krisna Bayu (Universitas Mataram, 2023)
Writing scientific papers at tertiary institutions is an obligation for students who will complete their studies. Every student should have the ability to write scientific papers, but in reality there are still many students who have difficulties. This is due to the limited ability of students to access references, as happened to students in class !A Study Program PAI FITK UIN North Sumatra Medan. Publish or Perish one application that can help students in finding references. Therefore, this service activity is carried out with the aim of providing training to students to improve students' ability to make scientific papers through Publish or Perish. Training activities begin with students being given Google Form to know the usage history Publish or Perish. Then delivery of material with lectures, questions and answers, and practice. The last evaluation is that students are given Google Form to see the results of the training. The result of this training activity is that as many as 38 students have skills in using Publish or Perish out of a total of 49 students who attended the training. With details of 17 quite capable students, 17 capable students, and 4 very capable students. Thus, from 34 students who had never used Publish or Perish because they did not have skills, after the training the 34 students had skills in operating Publish or Perish. While 4 students who were previously able to use Publish or Perish with the training to be very capable in using it. Thus it can be concluded that, with the training Publish or Perish Students gain knowledge and have skills in operating it.